Sintonizador e demodulador rápido de redes de Bragg - Toledo, Luiz Felipe Ribeiro Barrozo (2010)
This work describes the development of a device that can be used as a tunable filter based on a Fiber Bragg Grating or as an optical network switch. The device is made of a mechanical system used to compress the fiber optic in witchi the FGB is inscribed. The mechanical device uses a piezoelectrical multiplayer actuator. The device also contains a passive Fiber Bragg Grating interrogation system using a fixed filter based on a thin film. The device is studied with two FGB and the dynamical characteristics of the systems analyzed, especially the wavelength resolution and the tuning velocity. The device is also investigated using digital simulations and the results are compared with these simulations.